Partition coefficients of indoles and betacarbolines. - Guardado, P; Balon, M; Carmona, C; Muñoz, M; Domene, C (1997)
Partition coefficients for substituted indoles and betacarbolines were determined in octan-1-ol/water and cyclohexane/water. A comparative study of the results in both systems allows us to discuss the effects played by the different molecular structures, substituents, and aromaticity on the distribution properties of these compounds. In particular, the hydrogen-bond donor (HBD) and hydrogen-bond acceptor (HBA) properties of these solutes were characterized and compared with those of structurally related compounds. The Abraham solute descriptors were estimated and partition coefficients (log P) calculated and compared with the experimental values. The results show that the HBD properties are similar for indoles and betacarbolines, and the HBA capacity, as expected, is significantly enhanced by the contribution of the extra pyridinic or piperidinic ring in betacarbolines. The effects of the substituent groups are presented in relation to their contribution to the distribution properties of the compounds studied.